The Restoration and Renewal of the Palace of Westminster: Avoiding the Trap and Realising the Promise. Issue 3 (22nd July 2019) - Flinders, Matthew; Meakin, Alexandra; Anderson, Alexandra
Abstract: By failing to acknowledge the link between the design of our political institutions and growing levels of anti‐political sentiment, the restoration and renewal programme risks falling into a trap of its own making. Involving the public from the outset in an open review of the (re)design options for Westminster—in a positive and confident conversation—ensures the best opportunity for meaningful engagement between the public and the future of their democracy.